Plaque number board: visualizing the essence of exponents through simple proofs - Hapsari, Agnesi Alifia; Darmawan, Puguh (Nashir Al-Kutub Indonesia, 2025)
The exponential power rule was one of the materials studied at the high school level. Students tended to memorize it rather than understand it. This caused students to have difficulty in applying the concept of exponents when working on non-routine questions. The ability to prove the properties of exponents in a simple way was needed to improve students’ understanding, so a manipulative medium for the exponent power property called PLAKAT was created. This research aimed to examine the application of learning using the manipulative medium for the exponent power property known as PLAKAT. The research method used was qualitative with a case study approach. The instruments used to collect data included the manipulative media, video recording equipment, and observation notes. The subjects involved were practical students and audience students. The data collected consisted of video recordings and notes. The data were analyzed using interactive methods. The results of the research showed that this medium was useful for increasing students' understanding of the exponent power property. However, PLAKAT had a weakness: it did not have a rope, so it could not be hung, making its use less practical. This shortcoming served as a suggestion for teachers and students who intended to use this medium to prepare a more complete version to support smoother learning.